Attitude towards team-teaching - a study at Vietnam USA society English training service centre = - Hồ, Thị Hồng Hạnh (Can Tho University, 2009)
This study aims to investigate attitude of teachers and learners at elementary levels towards team-teaching at VUS, and basing on the findings, some suggestions will be made in order to better the teaching and learning system at the school.